1999
DOI: 10.1111/j.1574-695x.1999.tb01323.x
|View full text |Cite
|
Sign up to set email alerts
|

The nasopharyngeal bacterial flora in infancy: effects of age, gender, season, viral upper respiratory tract infection and sleeping position

Abstract: The aim of the investigation was to determine the effect of age, gender, viral upper respiratory tract infection (URTI), season and sleeping position on the composition of the nasopharyngeal bacterial flora in infancy. Seventy-two babies, 38 male and 34 female, whose birthdates were evenly spread throughout the year were followed from birth to 18 months of age. From 0 to 6 months nasopharyngeal swabs were obtained once a month in periods without URTI and daily for 3 days during episodes of URTI. From 12 to 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 22 publications
6
66
2
Order By: Relevance
“…Isolation of GABHS was significantly higher in group II patients of this present study as compared to Group I which is in line with the reports of Berkovitch et al [16] On the other hand isolation of NPM has been significantly higher in group I as compared to group II. The results of the present study are similar to the ones reported by Harrison et al [5] The significant increase in isolation of some of the PM in oropharynx with age further signifies the beneficiary and protective effect of breast feeding in infants. Reports clearly indicate that the mean age of first acquisition of PM like, S. pneumoniae, H.influenzae and M. catarrhalis is 6 months with a range of 1-30 months [7,8,13,14,[17][18][19].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Isolation of GABHS was significantly higher in group II patients of this present study as compared to Group I which is in line with the reports of Berkovitch et al [16] On the other hand isolation of NPM has been significantly higher in group I as compared to group II. The results of the present study are similar to the ones reported by Harrison et al [5] The significant increase in isolation of some of the PM in oropharynx with age further signifies the beneficiary and protective effect of breast feeding in infants. Reports clearly indicate that the mean age of first acquisition of PM like, S. pneumoniae, H.influenzae and M. catarrhalis is 6 months with a range of 1-30 months [7,8,13,14,[17][18][19].…”
Section: Discussionsupporting
confidence: 94%
“…being least seen in winter, all of which were found to be statistically significant (P<0.05). However, Harrison et al [5] reported no significant variation of bacterial colonization of infants in different seasons. Presence of a sibling less than 18 years of age was found to be significantly (p=0.005) associated with isolation of potentially pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that powerful inflammatory responses to common infectious agents or their products precipitate the physiologic events leading to SIDS [5][6][7]. Studies of adults and infants have also demonstrated that sleeping in the prone position increases the number and variety of organisms present in the upper respiratory tract [8,9]. In addition, when in the prone position, the temperature of the nasopharynx increases.…”
Section: Introductionmentioning
confidence: 98%
“…There is epidemiological data to support a role for bacteria in SIDS. Several studies have demonstrated significantly higher carriage of pathogenic, potentially toxigenic organisms in the upper respiratory tract of SIDS infants compared to healthy controls [3,4], particularly in children sleeping prone, a well established risk factor for SIDS [5]. Prone sleeping in children has also been shown to raise the nasal temperature (usually below 37°C), thereby potentially facilitating the persistence and/or growth of bacteria, as well as the induction of staphylococcal pyrogenic toxins, which requires a minimum temperature of 37°C [13].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…It has previously been reported that nasopharyngeal colonization with Staphylococcus aureus is significantly more common in SIDS infants compared to healthy controls, particularly in infants less than 3 months old [3,4], and that there is a positive association between S aureus carriage and prone sleeping, a recognized risk factor for SIDS [5]. A recent post-mortem study has also demonstrated a significantly higher prevalence of S aureus isolation from unexplained SUDI (SIDS) compared to explained SUDI deaths due to non-infective causes such as structural congenital heart disease or accidents [6].…”
Section: Introductionmentioning
confidence: 98%